The Myth of the Judgement of Paris in the Perspective of the Masonic Philosophical Thought: Vasily Maikov’s Narrative Poem “Суд Паридов” - Orłowska, Alina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
Myth, understood as allegory or an expression of human emotions, continuously redefines its content in the changing cultural context. In the poem analyzed here, the subtext of the narrative about the contest among the three goddesses of Olympus for the title of ‘the fairest’ is motivated by the Masonic worldview and serves explaining the Masonic concept of the Golden Age, based on the prevailing power of beauty (love), and harmony of force (power) and wisdom. Paris, by accepting the gift from Venus, yields to the imperfect sensuality and thus destroys the harmony of the world and engulfs it in chaos.